Sequencing and analysis of globally obtained human parainfluenza viruses 1 and 3 genomes - Bose, Michael E.; Shrivastava, Susmita; He, Jie; Nelson, Martha I.; Bera, Jayati; Fedorova, Nadia; Halpin, Rebecca; Town, Christopher D.; Lorenzi, Hernan A.; Amedeo, Paolo; Gupta, Neha; Noyola, Daniel E.; et al. (PloS one, 2019)
Human Parainfluenza viruses (HPIV) type 1 and 3 are important causes of respiratory tract infections in young children globally. HPIV infections do not confer complete protective immunity so reinfections occur throughout life. Since no effective vaccine is available for the two virus subtypes, comprehensive understanding of HPIV-1 and HPIV-3 genetic and epidemic features is important for diagnosis, prevention, and treatment of HPIV-1 and HPIV-3 infections. Relatively few whole genome sequences are available for both HPIV-1 and HPIV-3 viruses, so our study sought to provide whole genome sequences from multiple countries to further the understanding of the global diversity of HPIV at a whole-genome level. We collected HPIV-1 and HPIV-3 samples and isolates from Argentina, Australia, France, Mexico, South Africa, Switzerland, and USA from the years 2003-2011 and sequenced the genomes of 40 HPIV-1 and 75 HPIV-3 viruses with Sanger and next-generation sequencing with the Ion Torrent, Illumina, and 454 platforms. Phylogenetic analysis showed that the HPIV-1 genome is evolving at an estimated rate of 4.97 × 10-4 mutations/site/year (95% highest posterior density 4.55 × 10-4 to 5.38 × 10-4) and the HPIV-3 genome is evolving at a similar rate (3.59 × 10-4 mutations/site/year, 95% highest posterior density 3.26 × 10-4 to 3.94 × 10-4). There were multiple genetically distinct lineages of both HPIV-1 and 3 circulating on a global scale. Further surveillance and whole-genome sequencing are greatly needed to better understand the spatial dynamics of these important respiratory viruses in humans.